Faktor-Faktor yang Mempengaruhi Kemauan Wajib Pajak Orang Pribadi dalam Membayar Pajak pada Pasca Kebijakan Tax Amnesty - Sungkono, Sungkono; Sugiyanti, Slamet (JIFA (Journal of Islamic Finance and Accounting), 2018)
Many factors affect the willingness to pay taxes for taxpayers. Several previous studies have presented different results on these factors. This study aims to obtain empirical evidence about the factors that affect the willingness to pay taxes on the taxpayers of individuals who perform free work in DJP Kanwil DIY. Samples taken in the research as many as 100 taxpayers in the scope of 5 KPP in DIY. Data were collected through questionnaires and analyzed using multiple regression. The results showed that the variable awareness of paying taxes, knowledge and understanding of tax laws, perceptions of the effectiveness of the tax system, the quality of service tax officers and tax sanctions have a positive effect on the willingness to pay taxes. Keywords: tax awareness, tax knowledge, perception of the tax system, the quality of tax services, the willingness to pay taxes JEL Classification: E17, E62, H25, K34